Perbandingan Soft Skill Siswa dengan Menggunakan Model Jigsaw II dan CIRC - Israni Wedy Kurniati; Tedi Rusman; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2018)
This study aims to find out to compare the soft skills of students using jigsaw II and CIRC learning models in students of class VIII SMP Negeri 20 Bandar lampung academic year 2017/2018. The method used is quasi experiment with comparative approach. Technique of collecting data is through observation. The subjects of the study are students of class VIII SMP. The population in this study amounted to 350 people. The sampling technique in this research is cluster random sampling. Hypothesis testing uses two way analysis of variance and two independent sample t-test. The results showed that there is a difference of soft skill of the students using jigsaw II and CIRC learning model on the students of class VIII SMP Negeri 20 Bandar Lampung academic year 2017/2018. Penelitian ini bertujuan untuk mengetahui untuk membandingkan soft skill siswa menggunakan model pembelajaran  jigsaw II dan CIRC pada siswa kelas VIII SMP Negeri 20 Bandar lampung  Tahun Ajaran 2017/2018. Metode yang digunakan adalah eksperimen semu dengan pendekatan komparatif. Teknik pengumpulan data melalui observasi. Subjek penelitian yaitu siswa kelas VIII SMP. Populasi dalam penelitian ini berjumlah 350 orang. Teknik pengambilan sampel dalam penelitian ini adalah cluster random sampling. Pengujian hipotesis menggunakan analisis varian dua jalan dan t-test dua sample independen. Hasil penelitian menunjukkan bahwa ada perbedaan soft skill siswa menggunakan model pembelajaran jigsaw II dan CIRC  pada siswa kelas VIII SMP Negeri 20 Bandar lampung Tahun Ajaran 2017/2018.Kata kunci: CIRC,  jigsaw II, soft skill